Nafarroako ahozko mintzoaren aniztasuna - Ibarra Murillo, Orreaga (Huarte de San Juan. Filología y Didáctica de la Lengua, 2017)
Basque dialectal shows great diversity in Navarra; considerably higher than the surrounding languages. The analysis of various texts recorded at the end of the twentieth century shows this diversity of features. Some of these dialects are close to disappear. In this article we transcribe several texts, going from East to West, then we add a heading that summarizes the subject. The texts are usually transcribed following the conventions of the usual spelling; but they are given few concessions to the dialectal pronunciation. Next we add the dialectological analysis where outcrops own dialectal features of the different talks. Each text is accompanied by a phonological, morphological and syntactic analysis.